The Establishment of a Standard for Plasminogen (Glu-Type) - Gaffney, P J; Curtis, A D (Thrombosis and Haemostasis, 1984)
Following an international collaborative study, a preparation of glutamic acid-(glu-)human plasminogen was established as a British Standard. This study compared the activity of the proposed standard following full activation to plasmin with the 2nd International Reference Preparation (IRP) for plasmin using both fibrinolytic and chromogenic assays. There was good agreement between the results of the two assay methods. The activity of the standard was 10 units per ampoule, these units being equivalent to those defined by the 2nd IRP for plasmin.
Keywords: Plasminogen; Collaborative study; British Standard